Development and Validation of Postnatal Diet, Lactation, and Emotion Management (LEDies) Module - Rahmat, Nur Nazihah; Abdul Hamid, Syahrul Bariah; Ahmad Shuhaimi, Farhanah (Jurnal Gizi dan Pangan, 2024)
This study aims to develop and validate a module on managing diet, lactation, and emotion for postnatal mothers. This cross-sectional study involves three phases: needs assessment, module development, and module validation. About 37 mothers aged 18 to 49 years old with infants less than 6 months were recruited, and information on postnatal care practices, lactation knowledge, and emotion were obtained for module development. The guidelines from the Ministry of Health Malaysia and literature served as the foundation for the module that was developed following the requirements assessment utilizing the Health Belief Model (HBM). Content and face validity of the module is carried out to validate the developed module. The validation form used was adapted from Silveira de Castro (2007) which consists of seven criteria, two criteria related to content validity and another five criteria related to face validity. The content validity was assessed using a Content Validity Index (CVI). CVI was calculated using two different formulas: I-CVI and S-CVI. Meanwhile, a level of agreement was used in the data for the module's face. From the need assessment, most mothers with restricted seafood and nuts intake struggled to breastfeed and about 21.6% of them experienced postpartum depression. The developed module has been validated with both mean I-CVI and S-CVI more than 0.78 and 0.80, respectively. Meanwhile, five face validation components achieved 75% agreement, confirming the validity. In conclusion, the developed module named The LEDies has good validity and can serve as teaching material for postnatal mothers caring for themselves and their infants during the postpartum period.